Emotional Intelligence and Its Relationship with Workplace Accidents Among Employees of a Financial Institution in 2019 - Zubieta Burga, Luz de Maria (2025)
The main objective of the research was to determine the relationship between emotional intelligence and workplace accidents among the employees of a financial institution in 2019 given the high rate of workplace accidents due to personal factors. A sample of 70 employees was selected and the abbreviated Emotional Quotient Inventory (Bar-On EQ-i) was administered to them. Additionally, workplace accident investigation reports were reviewed to identify the main personal factors that caused workplace accidents. The study found a significant relationship between emotional intelligence and workplace accidents, with a rho value of −0.51. This shows an average negative correlation between emotional intelligence and workplace accidents, meaning that the variables are related to each other in an inversely proportional manner. In other words, the lower the level of emotional intelligence, the higher the number of workplace accidents.